2021
DOI: 10.2196/26505
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Implementation Context of a Telemedicine Service: Work Domain Analysis in a Surgical Setting

Abstract: Background A telemedicine service enabling remote surgical consultation had shown promising results. When the service was to be scaled up, it was unclear how contextual variations among different clinical sites could affect the clinical outcomes and implementation of the service. It is generally recognized that contextual factors and work system complexities affect the implementation and outcomes of telemedicine. However, it is methodologically challenging to account for context in complex health c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…A detailed account of specific findings is provided in “Modeling implementation context in telemedicine” [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A detailed account of specific findings is provided in “Modeling implementation context in telemedicine” [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…While this may seem obvious, these factors are beyond the control of the clinical staff and may interfere with teleguidance use over time. The WDA helped us identify and represent these types of issues in detail [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The service, called teleguidance, had shown success in a feasibility study [ 1 ], and health economic modeling showed its potential for improving clinical and economic outcomes [ 2 ]. Teleguidance practice was to be scaled up to 4 additional hospitals (5 in total including the first hospital), and efforts were made to understand the context into which the telemedicine intervention was introduced [ 3 ], and potential users’ attitudes toward the service prior to implementation [ 4 ]. This paper describes an investigation of practitioners’ experience of real-time use of teleguidance, based on surgeons’ expectations of how the service might contribute to performance and outcomes in a particular procedure, and their satisfaction with teleguidance immediately after the procedure.…”
Section: Introductionmentioning
confidence: 99%